Mortality, structure, propagation, and microhabitat characterization of Haageocereus acranthus: a case study on coastal lomas - Camel, Vladimir; Pillpa, Freddy; Colqui, Virginia; Ataucusi, Jose; Quispe-Huañahue, July; Felix, Edwin; Ninanya-Parra, Zulema; Maravi-Hinostroza, Key; Caysahuana, Keiko; Cabello-Torres, Rita (Frontiers in Plant Science, 2025)
The Haageocereus genus includes endemic species found in the coastal region of Peru and is characterized by varying ploidy levels that influence its shape and adaptability. It establishes itself in coastal lomas and desert ecosystems, capturing moisture from fog and reproducing through stem fragmentation and seeds to survive. Ecologically, it helps stabilize the soil and provides shelter and food for wildlife. The study aimed to propagate, evaluate mortality and structure, and characterize the microhabitat of Haageocereus acranthus in the coastal lomas of Mangomarca, Lima, Peru. To achieve this, three transects were established across an altitudinal gradient. The abundance, morphological data, and environmental factors (pH, cover, slope, organic matter, etc.) were assessed, and living and dead colonies were counted. Consequently, the stems grow approximately 4.8 cm per year under nursery conditions, while the roots develop 4.42 cm in 45 days. In a 4.41 ha area, 94 colonies were recorded, comprising 1,801 stems; 37.89% of the individuals had lengths between 20 and 40 cm. The largest stem reached a diameter of 8 cm and a length of 169 cm. Additionally, around 1,788 living colonies and 14,741 dead colonies were counted across all the lomas. The death of the cacti may be linked to anthropogenic pressure that has altered the soil from acidic to basic, increasing electrical conductivity while reducing the availability of organic matter and nutrients. Our research has also shown that pH and altitude influence the phenotypic characteristics of H. acranthus stems. At higher elevations, the size of the cacti increased alongside the amount of organic matter, while the concentration of carbonates decreased. Ultimately, mortality rates will likely rise due to severe human impacts, increasing temperatures, and prolonged droughts. Therefore, it is crucial to closely monitor and implement conservation and restoration measures for these coastal lomas endemic to South America.